Physicians’ Experience and Willingness to Participate in Non-Interventional Trials in Bulgaria - Emil Kostov; Evgeni Grigorov; Hristina Lebanova (Journal of Biomedical & Clinical Research, 2021)
Non-interventional studies (NIS) are conducted to obtain additional information about a medicinal product prescribed in the usual manner in compliance with the conditions determined in the marketing authorization. They are a valuable source of real-world data for the effectiveness and safety of medicines. This study aims to assess physicians‘ knowledge of non-interventional studies in Bulgaria and identify the primary factors and barriers hindering the NIS at a national level. An individual anonymous questionnaire with 16 items was distributed among physicians in inpatient and outpatient settings. The results showed that 81.3% (n=147) of the respondents have no experience with non-interventional studies. Physicians‘ willingness to participate in NIS in the future is high and independent of their previous experience. The main barriers hindering conducting NIS in Bulgaria are related to organization, the conduct and the design of the trials, and, sometimes, the investigators‘ concerns. There is a need for proper training of the researchers and expanding healthcare resources to grow the NIS sector in Bulgaria in line with the tendencies in Europe.